Staff nurses' adherence to oxygen therapy standards - Z. Rood-dehghan; M. Shaban; A. Memari; A. Mehran (Iran University of Medical Sciences, 2011)
Background and Aim : Oxygen therapy is a method in which oxygen is provided with more density than that in the atmosphere. Oxygen is used in the treatment of many diseases and since it is considered as a drug, it has to be prescribed and controlled like a drug. This research was done with the purpose of determining the observance of oxygen therapy standards by nurses before and during oxygen therapy.   Materials and method: In this descriptive study, 36 nurses, working in lung wards of the hospitals affiliated to Tehran University of Medical Sciences, were included in the study and their practice on oxygen therapy procedure was studied during the year 2006. Data collection tools were questionnaire and checklist and data collection methods were interview and observation. The researcher collected data on staff nurses practice of oxygen therapy, before and during the therapy, twice for each staff. Descriptive statistics were used to analyze the data.   Results: The performance before the oxygen therapy for all staff nurses (%96.3) was at a low level. Also, the performance during oxygen therapy for majority of staff nurses was at a low level. Conclusion: In general, many mistakes occur by staff nurses regarding oxygen therapy.